Between Hope and Reality: A Qualitative Exploration of Single Men’s Attitudes Toward Romantic Relationships - Sandra Handayani Sutanto; Pradipta Christy Pratiwi; Karel Karsten Himawan; Kartika Sari Dewi (Journal of Educational, Health and Community Psychology, 2026)
This study explores how single men in Indonesia make sense of romantic relationships amid competing expectations of intimacy and culturally embedded gender norms. Prior scholarship on singleness and relationship experiences has predominantly centred women’s perspectives, leaving men’s meanings and negotiations of romantic involvement less examined in depth. Using a qualitative design, we conducted a focus group discussion with five single men in Jakarta and analysed the data through reflexive thematic analysis. The findings indicate that participants generally endorsed relational ideals characterised by reciprocity, mutual support, and egalitarian partnership. However, these ideals were frequently complicated by the persistent influence of traditional gender-role expectations within their social environment, creating tensions between what participants regarded as desirable relationship practices and what they anticipated as normative—particularly in the transition from dating to marriage. Overall, the study highlights how patriarchal cultural scripts remain salient in shaping men’s expectations, role imaginaries, and relational negotiations. These insights suggest the value of relationship education and gender-awareness initiatives that address not only individual skills (e.g., communication and emotional openness) but also broader normative pressures that structure intimate life.